Dreamweaver CC for dummies - Warner, Janine, 1967- (Hoboken, New Jersey : For Dummies, a Wiley brand, 2013)
In this book fully updated version of Dreamweaver for Dummies, the author added a new chapter to show you how to create responsive web page designs that adjust to fit different screen sizes, using dreamweaver's fluid grid layout features.
Includes index
Tặng
Keywords: Dreamweaver (Computer file; Cloud computing; Dreamweaver; Web site development; Web sites -- Authoring programs; Web sites -- Design